Rare Case of Twin Reversed Arterial Perfusion Acardius Acephalus Subtype Seen in a Community-Based Hospital - Laura Reguero Cadilla; Carlos Villafuerte Santana; Nicolle Centazzo; Daniel Faustin (Thieme Medical Publishers, Inc., 2024)
Background TRAP sequence occurs in monochorionic pregnancies consisting of one normal fetus and a non-viable fetus. The pump twin has an increased risk of developing high-output cardiac failure.